Android and Forking Restrictions: On the Hidden Closedness of “Open” - Simonetta Vezzoso (Market and Competition Law Review)
The Google Android Decision was announced by the European Commission on 18 July 2018. The Commission found that three restrictions related to Android and Android apps that Google imposed on mobile device manufacturers and network operators infringed Article 102 TFEU. These restrictions, according to the Commission, “have enabled Google to use Android as a vehicle to cement the dominance of its search engine”. The Android Decision is not yet public. The prohibition of Google’s tying practices on the Android platform has already attracted significant attention by early commentators, also due to the proximity to other high profile antitrust cases. Against the backdrop of the still limited information available, the article proposes some first reflections on another conduct sanctioned by the Android Decision, namely Google’s forking restriction imposed on device manufacturers. In particular, the article describes a possible reasoning underpinning Google’s anti-fragmentation justification based on the economics of two-sided platforms. This justification stems from a purely “transactional view” of platforms. The article concludes that this view is only partially suitable to provide an accurate description of complex innovation ecosystems for the purposes of competition policy enforcement.